Rancang Bangun Sistem Informasi Kepegawaian Polres Metro Bekasi Menggunakan Metode V-Model - Hartanti, Dian (Jurnal Jaring SainTek, 2023)
The personnel information system is a system that records employees at the Bekasi City Metro Police. The problem of data collection at the Metro Jaya Regional Police is still not optimal, and there are no reminders for employees who will receive regular salary increases, promotions and employee pensions within the Bekasi City Metro Police, using the V-Model method which emphasizes validation/testing at each stage. system life cycle and user involvement in system development where users carry out system acceptance testing at the end of the development stage. The aim of this research is to create a Bekasi City Metro Police Employee Information system with Reminders (reminders) for Periodic Salaries, Promotions and Pensions, so that with this application employees will not need to be reminded repeatedly to collect data on requirements for promotions, periodic salaries and pensions., The expected results are that this information system will be useful for the Bekasi City Metro Police so that employee data collection can be maximized.